2014
DOI: 10.1186/2008-2231-22-17
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of anticholinesterase activity of some Iranian medicinal plants commonly used in traditional medicine

Abstract: BackgroundThe aim of this study was to evaluate acetylcholinesterase inhibitory activity of some commonly used herbal medicine in Iran to introduce a new source for management of Alzheimer’s disease. A total of 18 aqueous-methanolic extract (1:1; v/v) from the following plants: Brassica alba, Brassica nigra, Camellia sinensis, Cinchona officinalis, Citrus aurantifolia, Citrus x aurantium, Ferula assafoetida, Humulus lupulus, Juglans regia, Juniperus sabina, Myristica fragrans, Pelargonium graveolens, Pistacia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…84 Significant anticholinesterase activities of five Juniperus species from Turkey were studied by Orhan et al 3 In the other study, Jazayeri et al 85 reported that fruit of J. sabina had an anticholinesterase effect. 84 Significant anticholinesterase activities of five Juniperus species from Turkey were studied by Orhan et al 3 In the other study, Jazayeri et al 85 reported that fruit of J. sabina had an anticholinesterase effect.…”
Section: Enzyme Inhibitory Activitiesmentioning
confidence: 97%
“…84 Significant anticholinesterase activities of five Juniperus species from Turkey were studied by Orhan et al 3 In the other study, Jazayeri et al 85 reported that fruit of J. sabina had an anticholinesterase effect. 84 Significant anticholinesterase activities of five Juniperus species from Turkey were studied by Orhan et al 3 In the other study, Jazayeri et al 85 reported that fruit of J. sabina had an anticholinesterase effect.…”
Section: Enzyme Inhibitory Activitiesmentioning
confidence: 97%
“…Linalool (59 %) and linalyl acetate (23 %) constitute the major composition of the essential oil of Citrus aurantium [11]. Previous studies showed that Citrus aurantium plant had inhibitory effect on acetylcholinesterase [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reduced parasympathetic activity is another cause of PMS; inhalation of R. damascena essential oil increases the activity of the parasympathetic nervous system but reduces that of the sympathetic nervous system . R. damascensa has a proven anti‐acetylcholinesterase effect owing to the presence of compounds such as flavonoids . Improvements in the symptoms of PMS by inhalation of lavender and yuzu essential oils have also been shown to occur through increasing parasympathetic activity …”
Section: Discussionmentioning
confidence: 99%